In silico identification of auxiliary factors genes required for β-lactam resistance - Astudillo Skliarova, Igor Eduardo (2023)
Staphylococcus aureus is a type of bacteria commonly found on the skin and in the nasal passages of healthy individuals. However, it can also cause a range of infections in clinical settings. One of the most concerning aspects of S. aureus is its ability to develop antibiotic resistance. Methicillin-resistant S. aureus (MRSA) is a strain of the bacteria that is resistant to many antibiotics and can be difficult to treat. The primary mechanism of methicillin resistance in MRSA is the presence of the mecA gene, which encodes for a modified penicillin-binding protein known as PBP2a. This protein has a lower affinity for β-lactam antibiotics. Another gene, blaZ, is also present in MRSA and encodes for a β-lactamase enzyme that can hydrolyse and inactivate β-lactam antibiotics such as penicillin. In addition, there are several auxiliary factors that can contribute to β-lactam resistance. They can include efflux pumps, enzymes that modify or degrade antibiotics, and bacterial cell wall modifications that reduce the affinity of antibiotics for their targets. In this study, with the aid of the in silico identification method, we identify the novel auxiliary factors aux1, aux2, aux4, aux11, aux14, aux16 and aux19. Next, we show that aux2, aux4, aux11, aux14 are not directly involved in β-lactam resistance, but may contribute through other mechanisms that decrease the efficacy of these antibiotics, whereas aux16 and aux19 are directly associated with β-lactam and bacitracin resistance, respectively. Understanding the various auxiliary factors that contribute to beta-lactam resistance can help guide the development of new antibiotics and other therapeutic strategies.